State‐Level Unemployment and the Utilization of Preventive Medical Services. (16th July 2013) - Tefft, Nathan; Kageleiry, Andrew
<x xml:space="preserve">Abstract</x> Objective To study the association between macroeconomic conditions and preventive medical service utilization. Data Sources/Study Setting Secondary data collection of a survey of the civilian, non‐institutionalized population of adults (age 18 and older) in the United States between 1987 and 2010. Study Design Regression analyses that adjust for individual‐level demographic and socioeconomic determinants, state and time‐fixed effects, and state‐specific time trends. Data Collection/Extraction Methods State health departments, with technological and methodological assistance from the Centers for Disease Control and Prevention, conducted a cross‐sectional yearly telephone survey using a standardized questionnaire. Principal Findings The use of preventive medical services is procyclical: a 1 percentage point increase in the state‐level unemployment rate is associated with a 1.58 percent decrease in the quantity of distinct preventive care services utilized. Women and economically disadvantaged populations are shown to be especially sensitive to macroeconomic fluctuations. Conclusions Policy makers should be aware of cyclical changes in preventive care use, particularly among disadvantaged populations, when making challenging budgetary decisions during economic downturns. As physician recommendations can have a strong impact on patients' use, health care providers could increase efforts to persuade patients to seek screening exams and necessary vaccinations during periods of high unemployment.